Mending nuclear fences [arms control]. - Diakov, A.S (IEEE spectrum)
The end of the cold war brought with it the hope, and even the expectation, that the dreaded nuclear sword of Damocles would no longer hang over the heads of Russians, Americans, and, indeed, over all the world's peoples. Yet 10 years after the Berlin Wall was torn down, that hope seems further from being realized than before. Instead of the bold visions enunciated by President Mikhail Gorbachev and President Ronald Reagan-not to speak of the citizens and scientists urging them on-the world now witnesses foot-dragging on conclusion of agreements, nitpicking and haggling over details, and a deterioration of trust and even mutual comprehension. The authors discuss the reasons for this and discuss whether the deadlock on arms control can be broken. Possible courses of action that could be taken are outlined